A screening approach for the evaluation of tobacco-free 'modern oral' nicotine products using Real Time Cell Analysis. (2021) - East, N.; Bishop, E.; Breheny, D.; Gaca, M.; Thorne, D.
Graphical abstract: Highlights: Tobacco-free nicotine pouches are an emerging nicotine product category. RTCA provides a real-time assessment of the potential cytotoxicity of these products. Gingival fibroblasts and epithelial cells showed comparable responses. The BAT products assessed showed little to no cytotoxicity, with increasing flavours and nicotine strengths. RTCA could differentiate between a commercial product and a reference snus product. Abstract: In many regulated industries there is an increasing pressure to provide timely and robust risk assessment data to support product launches. Real-time cell analysis (RTCA) is a tool that allows for the fast and relatively labour-free cytotoxic assessment of test compounds, compared to traditional methods. Here, we propose an application for the RTCA platform to provide a screening approach, to evaluate the cytotoxic potential of tobacco-free nicotine pouches, also termed modern oral product (MOP), to determine the contribution of differing nicotine strengths (4−11 mg) and a range of available flavour types from multiple markets, on overall product toxicity. Aqueous extracts were prepared for all products using 1 pouch in 20 mL cell culture media and applied to the cell system for 24 h. Test extract nicotine concentrations reflected the increases in product nicotine strength; however, these changes were not present in the same magnitude in the cytotoxicity data obtained from both primary human gingival fibroblasts (HGF) and an NCI-H292 human bronchial epithelial continuous cell line. Furthermore, across the range of flavours and product nicotine strengths tested, H292 cells whilst not the target organ for oral product use, accurately predicted the results seen in HGFs and could be considered a useful surrogate for fast screening studies. H292 cells are more easily cultured and for longer periods, offering a more compatible test system. In conclusion, the data demonstrate the utility of the RTCA platform for the quick assessment of a large range of product variants. Furthermore, for a cytotoxicity measure with this test product, the simple H292 cell line can predict outcomes in the more complex HGF and provide useful pre-clinical cytotoxicity screening data to inform the risk assessment of MOPs and the relative contribution of flavourings, nicotine and other components.